The morphological and biochemical investigation of electromagnetic wave effects on urinary bladder in prenatal rats - (:unkn) unknown (MARMARA UNIV, FAC MEDICINE, 2017)
Objectives: The aim of the study was to investigate the effects of digital cellular system (DCS) 1800-MHz radiation of a common digital mobile phone which has the highest specific absorption rate value of 1.79 W/kg on the urinary bladders of male rats. Materials and Methods: Rats exposed to electromagnetic wave (EMW) emitted by mobile phones on stand-by (Stand-by Fetal Group) or discontinious transmission mode (EMW Fetal group), 2 hours per day, from embryonic day 14 until parturition or until postnatal day 60 (Stand-by Fetal Group). The urinary bladders of the animals in experimental groups were removed at postnatal day 60 and prepared for light and electron microscopical investigation. The barrier function of urothelium was evaluated using zonula occludens 1 and E-cadherin immunohistochemistry and ruthenium red staining for transmission electron microscopy. Oxidative damage was evaluated by biochemical techniques. Results: EMW wave group showed desquamation of urothelial cells, increased number of mast cells, degeneration of tight junctions and dilatation of intercellular space. Finally, increase in the malondialdehyde and decrease in the glutathione levels were observed in all experimental groups when compared to those in the control group. Conclusion: Exposure intensity and time length correlate with adverse effects in developing period of the urinary bladder. These changes may lead to urinary bladder inflammatory disorders.
Keywords: Cellular phone; Electromagnetic wave; Urinary bladder; ZO-1; E-cadherin; INTERSTITIAL CYSTITIS; MOBILE PHONE; CELL; FREQUENCY; RADIATION; FIELDS; MODULATION; EXPRESSION; EXPOSURE; BARRIER